Chronic pulmonary aspergillosis: rationale and clinical guidelines for diagnosis and management. Issue 1 (23rd December 2015) - Denning, David W.; Cadranel, Jacques; Beigelman-Aubry, Catherine; Ader, Florence; Chakrabarti, Arunaloke; Blot, Stijn; Ullmann, Andrew J.; Dimopoulos, George; Lange, Christoph
ERS and ESCMID guideline for the management of chronic pulmonary aspergillosis released http://ow.ly/Tzlsu Chronic pulmonary aspergillosis (CPA) is an uncommon and problematic pulmonary disease, complicating many other respiratory disorders, thought to affect ∼240 000 people in Europe. The most common form of CPA is chronic cavitary pulmonary aspergillosis (CCPA), which untreated may progress to chronic fibrosing pulmonary aspergillosis. Less common manifestations include: Aspergillus nodule and single aspergilloma. All these entities are found in non-immunocompromised patients with prior or current lung disease. Subacute invasive pulmonary aspergillosis (formerly called chronic necrotising pulmonary aspergillosis) is a more rapidly progressive infection (<3 months) usually found in moderately immunocompromised patients, which should be managed as invasive aspergillosis. Few clinical guidelines have been previously proposed for either diagnosis or management of CPA. A group of experts convened to develop clinical, radiological and microbiological guidelines. The diagnosis of CPA requires a combination of characteristics: one or more cavities with or without a fungal ball present or nodules on thoracic imaging, direct evidence of Aspergillus infection (microscopy or culture from biopsy) or an immunological response to Aspergillus spp. and exclusion of alternative diagnoses, all present for at least 3 months. Aspergillus antibody (precipitins) is elevated in over 90% of patients. Surgical excision of simple aspergilloma is recommended, if technically possible, and preferably via video-assisted thoracic surgery technique. Long-term oral antifungal therapy is recommended for CCPA to improve overall health status and respiratory symptoms, arrest haemoptysis and prevent progression. Careful monitoring of azole serum concentrations, drug interactions and possible toxicities is recommended. Haemoptysis may be controlled with tranexamic acid and bronchial artery embolisation, rarely surgical resection, and may be a sign of therapeutic failure and/or antifungal resistance. Patients with single Aspergillus nodules only need antifungal therapy if not fully resected, but if multiple they may benefit from antifungal treatment, and require careful follow-up.